(untitled) (Revista de Ciências Agroveterinárias, 2011)
The history of soil use by forests during XX century in Campos de Lages region, Santa Catarina state, Brazil was studied. The changes in the soil use and its relations to sociotechnical contexts have been approached, along with how these relations have affected the meaning and the value of forest soils in the Regions history. To understand the relations among soils, forests and society, a conceptual arrangement was used based on Actor-network Theory (ANT). Since the early XIX Century, when the Region insertion in Minas Gerais network through the tropeirismo occurred, cattle creation has been the typical scenario of the native landscape use. In 1940´s, changes on sociotechniques initiated the “cycle of the pine”, with intense Araucaria angustifolia wood exploitation. At the end of XX Century, the “soil forest vocation” was modified by forestry. However, existing controversies about the reforestations might change the meaning of the soil used by forests, creating a new confl ict. The study concludes that the forest use was more diverse. The forest soil had assumed distinct meanings for different actors in the course of time, although keeping the same sociallogic of land use.